BRAF somatic mutation contributes to intrinsic epileptogenicity in pediatric brain tumors. (November 2018) - Koh, Hyun; Kim, Se; Jang, Jaeson; Kim, Hyungguk; Han, Sungwook; Lim, Jae; Son, Geurim; Choi, Junjeong; Park, Byung; Heo, Won; Han, Jinju; Lee, Hyunjoo; et al.
Abstract Pediatric brain tumors are highly associated with epileptic seizures1 . However, their epileptogenic mechanisms remain unclear. Here, we show that the oncogenicBRAF somatic mutation p.Val600Glu (V600E) in developing neurons underlies intrinsic epileptogenicity in ganglioglioma, one of the leading causes of intractable epilepsy2 . To do so, we developed a mouse model harboring theBRAF V600E somatic mutation during early brain development to reflect the most frequent mutation, as well as the origin and timing thereof. Therein, theBRAF V600E mutation arising in progenitor cells during brain development led to the acquisition of intrinsic epileptogenic properties in neuronal lineage cells, whereas tumorigenic properties were attributed to high proliferation of glial lineage cells. RNA sequencing analysis of patient brain tissues with the mutation revealed thatBRAF V600E -induced epileptogenesis is mediated by RE1-silencing transcription factor (REST), which is a regulator of ion channels and neurotransmitter receptors associated with epilepsy. Moreover, we found that seizures in mice were significantly alleviated by an FDA-approved BRAFV600E inhibitor, vemurafenib, as well as various genetic inhibitions ofRest . Accordingly, this study provides direct evidence of aBRAF somatic mutation contributing to the intrinsic epileptogenicity in pediatric brain tumors and suggests that BRAF and REST could be treatment targets for intractable epilepsy. In pediatric brain tumors that are accompanied by epileptic seizures, theBRAF somatic mutation V600E contributes to intrinsic epileptic properties in neurons, which can be suppressed by vemurafenib in mice.